PENAFSIRAN AKTIVIS FEMINIS TERHADAP AYAT WARIS (PEMIKIRAN SITI MUSDAH MULIA DAN AMINA WADUD TERHADAP Q.S AN-NISA AYAT 11): PENAFSIRAN AKTIVIS FEMINIS TERHADAP AYAT WARIS (PEMIKIRAN SITI MUSDAH MULIA DAN AMINA WADUD TERHADAP Q.S AN-NISA AYAT 11) - Aziz, Dedi Abdul (Takafu: Journal of Tafsir and Gender Perspective, 2024)
The division of inheritance which refers to inheritance verses still leaves unresolved problems, such as the 2:1 division between men and women which is considered gender biased. Surah al-Nisa/4: 11 which explains that men's share is twice that of women is the maximum limit. Under certain conditions a woman has the potential to have more shares. This research aims to determine the distribution of inheritance. This research method uses a type of library research. Library research or library research using methods of collecting library data, reading, taking notes and processing research materials. This research uses a qualitative approach because the data source and research results in the library research that the researcher will carry out are in the form of descriptions of words. The results of this research show that the main principle that must be guided by the distribution of inheritance in Islamic law is justice. The most prominent provision in the inheritance distribution system in Islamic law is found in Surah al-Nisa/4: 11, where one man's share is the same as the share of two women or in a ratio (2:1), textually this provision does seem unfair and exclude women more. However, the justice contained in this verse is not justice based on numbers and quantities, but by looking at the functions, duties, roles and responsibilities of men and women. The portion of justice for humans is certainly different from justice in the eyes of Allah SWT.